Prevalence and investigation of Cytomegalovirus (HCMV) in blood donors from the main blood establishment in Rio de Janeiro/Brazil - Agildo da Silva Oliveira; Jéssica Gonçalves Pereira; Gabrielle Tantos Nunes; Ivanildo Pedro de Sousa Junior; Dmitry José de Santana Sarmento; Josiane Iole França Lopes; Luiz Amorim Filho; Vanessa Salete de Paula (Brazilian Journal of Infectious Diseases)
Background: Human Cytomegalovirus (HCMV) remains a significant cause of morbidity and mortality among pregnant women and immunocompromised patients. HCMV transmission can occur through blood transfusions and typically results in asymptomatic infections in newborns and young individuals or causes symptoms like infectious mononucleosis when symptomatic infections arise. HCMV infection poses a notable risk to transfusion recipients, particularly in vulnerable groups such as premature newborns and immunosuppressed patients. The risk persists even after prophylaxis ends, especially in patients who undergo organ transplantation and receive blood or blood products from a seropositive donor while being seronegative themselves (D+/R-). Materials and methods: Here, we investigated the serological and molecular prevalence of HCMV among 980 blood donors from the main blood bank in Rio de Janeiro, Brazil, using chemiluminescence and real-time PCR (TaqMan). The data underwent univariate, bivariate, and multivariate statistical analyses using the SPSS program, version 20.0. Results: The average age of donors was 38.53 years, with a majority being male (53.9 %). The prevalence of cytomegalovirus was 88.5 %, and HCMV DNA was detected in 1.2 % of the samples. Discussion: Given that there are approximately 100,000 blood donations per year, this prevalence rate is considerably high compared to that in developed countries. These findings underscore the critical need for ongoing surveillance and molecular testing to ensure the safety of blood supplies.